IMPROVING STUDENTS’ ABILITY IN WRITING RECOUNT TEXT USING DIARY AT ONE OF JUNIOR HIGH SCHOOL IN CAMPAKA – CIANJUR - Suryaman, Yaman (IKIP Siliwangi, 2018)
In mastering English, students find problems dealing with language skill and language components, most students in Indonesia consider English as a difficult subject which make them frustrated. Writing is one of the four language skills that play a very important role in second language learning. Writing skill is more complex and difficult to teach, requiring the mater not only the grammatical and theoretically devices but also the conceptual. One of the equipment aids that can be used in learning writing is a diary. The main objective of this study is to find out whether writing diary improves students’ writing skill or not. In this research, the researcher used the quantitative method, with classroom action research design. The population of this study was all students of class 8A that consisted of 30 students. Observation, interview, and test as the instruments of this research. The researcher compared the achievement of pre-test to identify the effectiveness of using diary writing.